Subalgebras of the Poincare algebra AP (2, 3) and symmetry reduction of the nonlinear ultrahуperbolic d’Alambert equation. I - Barannik , L. F.; Lagno , V. I.; Fushchich , V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1988)
-